Esprit et corps chez Descartes - Glauser, Richard (My University, 1996)
Glauser examines Baertschi's analysis of the mind-body problem in Descartes (Les rapports de l'ame et du corps, Vrin, Paris, 1992). Baertschi's interpretation is accurate and thorough. Glauser elaborates on three issues. Baertschi does not sufficiently clarify to what extent he rejects Ryle's analysis of the sources and nature of Descartes's dualism. One should compare Descartes's mind-body real distinction with scholastic accounts of the real distinction, such as is to be found in Suarez's seventh Dispute. Glauser discusses Baertschi's thesis according to which the soul has an "essential disposition" to be united to a human body.
Keywords: Body. Dualism. Metaphysics. Mind.